ANALISIS PENYUSUNAN ANGGARAN PENJUALAN PADA UMKM KULINER SEBLAK RANCAEKEK - Lia Nurjanah; Rachmat Agus Susanto (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2024)
This research was conducted because there was no budget in the financial records of Seblak Rancaekek Culinary MSMEs, especially the sales budget where the sales budget is a budget that plans the company's sales for the coming period. The sales budget is used as a company tool in planning and controlling the company's sales activities in order to achieve the desired optimal profit. The sales budget can be used as a reference in efforts to increase subsequent sales. In making sales forecasts, researchers compared 3 forecasting methods, namely Semi Average, Trend Moment, and Least Square and calculated the Standard Forecasting Error (SKP) for each method to determine the most appropriate method.